EndGame for Corruption - A DPE-Based Framework to Support the Design of Serious Games for Fight Against Corruption - Abreu, Vinicius Santos de (2023)
Corruption, a pervasive issue that affects societies globally, is closely linked to inequality and the inadequate provision of public services. In this context, where the population is the primary victim, serious games are utilized to raise awareness, aiming to empower individuals and strengthen their role as vigilant citizens. Game designers strive to develop solutions that facilitate learning and reflection on corruption. This article proposes an adaptation of the Design Play and Experience Framework, referred to as the Endgame for Corruption Framework (EgC Framework). This adaptation incorporates the reflection process and is guided by the learning objectives mapped from Bloom’s Taxonomy. The EgC Framework is the basis for designing a game that immerses players in a corrupt context. We conducted a quasi-experimental study to evaluate the game’s effectiveness and gathered participants’ perceptions through a survey questionnaire. The collected data underwent both quantitative and qualitative analyses. The results demonstrated clear indications of player dissatisfaction and reflection on the situations presented in the game. These findings provide valuable evidence of the game’s impact in prompting players to engage critically with corruption. Overall, this research showcases the potential of serious games in addressing the issue of corruption. The EgC Framework, combined with thoughtful design choices and evaluation methods, contributes to the development of games that foster awareness and reflection among players.